2019
DOI: 10.3389/fpsyg.2019.00530
|View full text |Cite
|
Sign up to set email alerts
|

The Binge Eating Scale: Structural Equation Competitive Models, Invariance Measurement Between Sexes, and Relationships With Food Addiction, Impulsivity, Binge Drinking, and Body Mass Index

Abstract: Introduction: The Binge Eating Scale (BES) is a widely used self-report questionnaire to identify compulsive eaters. However, research on the dimensions and psychometric properties of the BES is limited. Objective: The aim of this study was to examine the properties of the Spanish version of the BES. Methods: Confirmatory Factor Analyses (CFAs) were carried out to verify the BES factor structure in a sample of Spanish college students ( N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 59 publications
3
29
0
2
Order By: Relevance
“…As regards the mediation variables, they included: Binge eating. This variable was assessed using the total score on the Binge Eating Scale (BES; [56]; Spanish version: [57]). The BES is a 16-item self-report questionnaire designed to identify the symptoms associated with binge eating (eating large amounts of food in a short time and feeling loss of control).…”
Section: Methodsmentioning
confidence: 99%
“…As regards the mediation variables, they included: Binge eating. This variable was assessed using the total score on the Binge Eating Scale (BES; [56]; Spanish version: [57]). The BES is a 16-item self-report questionnaire designed to identify the symptoms associated with binge eating (eating large amounts of food in a short time and feeling loss of control).…”
Section: Methodsmentioning
confidence: 99%
“…The BES measures the behavioral aspects of binge eating, as well as the feelings and thoughts associated with such behavior [26] . It is a self-administered questionnaire composed of 16 multiple choice items: Eight items that describe behavioral manifestations (for example, eating fast or consuming large amounts of food) and eight items on associated feelings and cognitions (for example, fear of not stopping eating) [27] . Each item has a response range from 0 to 3 points (0 = no severity of the BES symptoms, 3 = serious problems of the BES symptoms).…”
Section: Binge Eating Behaviourmentioning
confidence: 99%
“…Since the degree of perceived stress varies in individuals, understanding characteristics of people who have less stress tolerance and are highly reactive to stress is important [ 39 ]. Research has shown that individuals with high impulsivity levels are more likely to result in obesity [ 40 , 41 , 42 ], and activities such as exercise, music, and meditation can help sooth emotions and avoid overeating [ 43 ]. Although the content of FA has been debated over whether it is more of a “substance addiction” or a “behavior addiction” [ 43 , 44 ], pharmacologic therapy and cognitive behavioral therapy are both believed to be effective ways to treat substance addiction and addictive behaviors, and were proven to elevate the efficiency when both therapies were applied as treatment [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%